I have an integro-differential equation of the following form: $$ \frac{dx}{dt} = a_0 + (a_1+a_2x(t))e^{-a_3 \int_0^t x(s)} + a_4x(t) $$ In an attempt to solve this equation, I transformed it first to an equation of the form $$ \frac{d^2g}{dt^2} = a_0 + (a_1+a_2 \frac{dg}{dt})e^{-a_3 g(t)} + a_4\frac{dg}{dt}, $$ by defining $g(t) = \int_0^t x(s)ds$ (I know that $x(s)>0$ for all $s$) and then to an equation of the form $$ u(g)\frac{du}{dg} = a_0 + (a_1+a_2 u(g))e^{-a_3 g} + a_4u, $$ by defining $u(g) = \frac{dg}{dt}(t(g))$ (since g(t) is monotonically increasing, it is invertible). Then further substituting $h=u^2$, I get an equation of the form $$ \frac{dh}{dg} = b_0 + b_1 h^{\frac{1}{2}} + (b_2 h^{\frac{1}{2}} + b_3)e^{b_4g}. $$

I am stuck here however. The "homogenous" part of this equation is solvable with solution of the form $$ h_{hom} = b_1g + \frac{b_2}{b_4}e^{b_4g} + c_0, $$ but I am not sure how to proceed from here since the equation is not-linear. Also in general $b_0=b_2$ and $b_1 \neq b_2$ so the equation is not seperable as well.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.